Conventional and alternative disinfectants on the development of Cándida Albicans : In vitro effect - Vásquez Lizama, Giannina; Ramos Pazos, Nicolás; Yefi Carrasco, Roger (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Cándida Albicans is a commensal fungus that colonizes various surfaces of the body, including the oral mucosa. It has the ability to transition to pathogen in the face of any change in its environment. Forms biofilms resisting various chemical disinfectants. The aim of this study was to evaluate the in vitro efficacy of conventional disinfectants and alternative disinfectants on the development of Cándida Albicans. Alternative disinfectants of cinnamon oil and clove have significantly greater efficacy than conventional sodium hypochlorite disinfectant (p<0.001), which may suggest their use as disinfectants on surfaces contaminated with Cándida Albicans.